Prescribing pattern in outpatient department of neurosurgery in a tertiary care hospital of North India - Tabassum, Rehana; Hussain, Syed Sajad; Arif, Sajad Hussain; Ramzan, Altaf; Farhat, Samina (International Journal of Research in Medical Sciences, 2019)
Background: The neurosurgical disorders are amongst the leading cause of global mortality and morbidity. Though surgical intervention is thought to be the main management protocol in the neurosurgical setup but drugs are being equally used especially in the outpatient setting. The present study was carried out in view of the sparse data available on prescribing pattern in neurosurgery. Methods: The present study was conducted by the department of pharmacology in outpatient department of neurosurgery in a tertiary care centre to look into the prescription pattern among these patients. Results: In 268 patients analyzed, mean age was 43.02±15.93 years and 52.23% were females. Majority of our participants (44%) were found to be of young to middle age group (21-40 years). The diagnosis among the study population was spread over large number of diseases. Lumbar Disc Prolapse (LDP) was found to be the leading cause of neurosurgical morbidity, amounting to 32%. As far as the prescription of various drugs in the outpatient of neurosurgery is concerned, Analgesics were the most common drugs prescribed constituting about 48% of the total drugs prescribed followed by GABA analogues and multivitamins which equally formed 41% of the total prescribed drugs. Conclusions: Although the prescription pattern studies among the outpatient neurosurgery patients are very scant, the analysis of prescription studies will be helpful to encourage the rational drug prescribing pattern.